2014
DOI: 10.1021/ac502217r
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Imaging of Cassette-Dosed Drugs for Higher Throughput Pharmacokinetic and Biodistribution Analysis

Abstract: Cassette dosing of compounds for preclinical drug plasma pharmacokinetic analysis has been shown to be a powerful strategy within the pharmaceutical industry for increasing throughput while decreasing the number of animals used. Presented here for the first time is data on the application of a cassette dosing strategy for label-free tissue distribution studies. The aim of the study was to image the spatial distribution of eight nonproprietary drugs (haloperidol, bufuralol, midazolam, clozapine, terfenadine, er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 23 publications
1
96
0
Order By: Relevance
“…40 Meanwhile, LESA MS/MS experiments performed in MRM mode have been used for imaging drugs in tissue sections with a spatial resolution of ~1 mm. 97 Key findings from these studies will be discussed in the next sections.…”
Section: Tandem Mass Spectrometry Imagingmentioning
confidence: 97%
See 2 more Smart Citations
“…40 Meanwhile, LESA MS/MS experiments performed in MRM mode have been used for imaging drugs in tissue sections with a spatial resolution of ~1 mm. 97 Key findings from these studies will be discussed in the next sections.…”
Section: Tandem Mass Spectrometry Imagingmentioning
confidence: 97%
“…97 To increase throughput and potentially reduce costs, Swales et al simultaneously administered four drugs to a rat model. 97 MSI was performed on rat brain and kidney tissue sections post drug administration at two time points. Figure 6G shows LESA MS/MS images of four drug compounds in rat kidney at 2 and 6 hours post dosing.…”
Section: Localized Analysis and Imaging Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, high resolution MSI provided a significant advantage of autoradiography from the aspect of the drug metabolites (Fehniger et al 2011;Jirasko et al 2014;Liu et al 2013;Buck et al 2015) and demonstrated the distribution of a confirmed drug metabolite that possibly lead to the drug toxicity (Török et al 2015). The technology is today making important contributions in fields such as PK screening (Castellino et al 2013), novel pro-drug concepts (Nilsson et al 2010;Fehniger et al 2011), drug delivery systems (DDS) by micellar nanoparticle formulation (Swales et al 2014), biomarkers for PD (Yasunaga et al 2013;Shariatgorji et al 2014;Cobice et al 2013) as well as proteomics (Goto et al 2014;Ye et al 2014). MSI ultimately leads to a better understanding of ADME, PK/PD and TK/TD.…”
Section: Drug Metabolism and Pharmacokinetics (Dmpk)mentioning
confidence: 99%
“…LESA-MSI is a surface sampling technique that has been shown to be widely applicable and sensitive but can deliver only low spatial resolution images (typically 1000 μm)11. The technique can be combined with Orbitrap or time of flight mass spectrometers for effective use as a profiling tool15 but has also been used effectively with high sensitivity triple quadrupole mass spectrometers operated in selected reaction monitoring mode for mass spectrometry imaging16.…”
mentioning
confidence: 99%